Białoruskie i ukraińskie identyfikacje kultury polskiej - Garncarek, Piotr (Postscriptum Polonistyczne, 2020)
The article presents aspects related to the perception of the Polish culture by foreign students of the University of Warsaw. Comments by representatives of these nations, with whom we share a common history and a Slavic ethnic characteristic, became the basis for deliberations. Aspects are also addressed here related to migration to Poland, its causes and characteristics. The analysis covered cultural knowledge about Poland, ways of perceiving the shared history and mental differences mentioned by foreign students coming from the eastern territories of the First Republic of Poland.